2020
DOI: 10.22267/rus.202203.199
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout en docentes de Latinoamérica: Una revisión sistemática

Abstract: Introducción: El Síndrome de Burnout (SB) se entiende como un fenómeno que incluye cansancio emocional, despersonalización y reducida realización personal, generando consecuencias multivariadas a nivel físico, psicológico, social y laboral. Objetivo: Identificar la producción bibliográfica en Latinoamérica sobre el SB en docentes en el período comprendido entre los años 2008 a 2018. Materiales y métodos: Revisión sistemática de literatura basada en las directrices PRISMA-P. Se realizó un rastreo bibliográfico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 42 publications
0
5
0
11
Order By: Relevance
“…Despite these valuable efforts, most systematic reviews have either ignored research produced in Latin America completely or focused only on one occupation and a few categories of psychosocial risks (e.g. Monroy-Castillo & Juárez-García, 2019;Tabares-Díaz et al, 2020), all of which has contributed to produce biased and scattered evidence of this relationship. Thus, the present article contributed to the field of organizational psychology by critically examining the Latin-American literature that investigates the relationship among a wide variety of psychosocial risks, individuals' health, and organizational performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these valuable efforts, most systematic reviews have either ignored research produced in Latin America completely or focused only on one occupation and a few categories of psychosocial risks (e.g. Monroy-Castillo & Juárez-García, 2019;Tabares-Díaz et al, 2020), all of which has contributed to produce biased and scattered evidence of this relationship. Thus, the present article contributed to the field of organizational psychology by critically examining the Latin-American literature that investigates the relationship among a wide variety of psychosocial risks, individuals' health, and organizational performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is worth noting that most systematic reviews of this relationship (e.g., Franklin & Gkiouleka, 2021;Lang et al, 2012) have considered only papers in English, indexed in international databases, such as the Web of Science, thus ignoring to a considerable extent studies conducted in Latin America. Furthermore, most systematic reviews of this relationship that do include Latin-American studies have focused on only one profession or occupation and one kind of psychosocial risk (see Monroy-Castillo & Juárez-García, 2019;Tabares-Díaz et al, 2020), which also contributes to producing scattered empirical evidence of this relationship. In this sense, because psychosocial risks affect all positions and professions and, therefore, may be considered a global issue, a comprehensive systematic review of the studies involving all kinds of occupations and professions that examine the effects of a wide variety of psychosocial risks on individuals' health and organizational performance remains vital to, on the one hand, provide evidence of the cultural validity of the results of Anglo-Saxon research, and, on the other hand, design preventive strategies that consider the particularities of the Latin-American context (see considerations in Kortum & Leka, 2014;Kortum et al, 2010).…”
Section: Palabras Clavementioning
confidence: 99%
“…Para la variable dependiente se utilizarán los datos obtenidos con el Maslach Burnout Inventory o MBI (Maslach et al, 1997) ampliamente utilizado para medir la prevalencia del Burnout (Pinel-Martínez et al, 2019;Tabares-Díaz et al, 2020). Consta con 22 ítems valorados con una escala de Likert de siete grados.…”
Section: Muestra Y Levantamiento De Datosunclassified
“…Furthermore, previous research involving teachers at different educational levels has identified factors affecting teachers in the workplace. These should be considered when addressing risk reduction and burnout prevention (Carlotto and Câmara, 2017 ; Tabares-Díaz et al, 2020 ). The above mentioned factors include interpersonal variables such as emotional expression and regulation, motivation, self-efficacy, and teacher engagement (García-Renedo et al, 2006 ; Perandones-Gonzalez et al, 2014 ; Lozano-Paz and Reyes-Bossio, 2017 ).…”
Section: Positive Psychology In Teachers' Well-beingmentioning
confidence: 99%